The role of Christian leadership in the workplace in China ----A case study of a medium-sized enterprise in Chinese service industry - Wang, Jing (2013)
This article examines religious leadership in workplace. It focuses on the practice of Christian leadership in Chinese business context. It attempts to, firstly, explore why employers adopt Christian leadership and promote Christian values in workplaces, and secondly, investigate employees’ reactions and understanding of the presence of Christian leadership in their organizations. The research is based on a private medium-sized enterprise in Chinese service industry of which the leader adopts Christian leadership. Semi-structured interviews and direct observation method are used. The findings shows that Christian leadership is adopted to promote morality and organizational ethical behavior, motivate staffs, construct community, maintain staffs etc. Reactions of employees towards Christian leadership vary from person to person, and include both acceptances and rejections